2x+13=41-7x

Simple and best practice solution for 2x+13=41-7x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+13=41-7x equation:


Simplifying
2x + 13 = 41 + -7x

Reorder the terms:
13 + 2x = 41 + -7x

Solving
13 + 2x = 41 + -7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7x' to each side of the equation.
13 + 2x + 7x = 41 + -7x + 7x

Combine like terms: 2x + 7x = 9x
13 + 9x = 41 + -7x + 7x

Combine like terms: -7x + 7x = 0
13 + 9x = 41 + 0
13 + 9x = 41

Add '-13' to each side of the equation.
13 + -13 + 9x = 41 + -13

Combine like terms: 13 + -13 = 0
0 + 9x = 41 + -13
9x = 41 + -13

Combine like terms: 41 + -13 = 28
9x = 28

Divide each side by '9'.
x = 3.111111111

Simplifying
x = 3.111111111

See similar equations:

| 7-9x=87-23x | | 2(2-x)=(x+3) | | -4-3x=14-19x | | 6=-10-p/5 | | -4(x+5)=28 | | 0-5=6-7x | | 0-5x=-7x | | -48=6(a-1) | | x+2x+x+25=165 | | 4+7x=34-x | | -57=-5x+8(3+4x) | | 5+8m=-1+5m | | 6x-5=4x-53 | | y=.666x-1 | | 6x-4x+7=0 | | 4x-2(x+3)=3x | | 63=-7(3n-3) | | X=-3.6X^2-8.8X+8.3 | | 6x-3(4+x)=0 | | 4x=-25 | | 47533.32=2*3.14*r^2+2*3.14*r*232 | | f/5+4=29 | | -2(9-3x)+2=-4 | | -73=6m-5(m-3) | | 7-3(2-x)+6=-2 | | 72*64-7/80+4*x=40*52*2 | | -6(x-3)-8=-8 | | 3265+28=oshawn | | 4=4a-8(a-2) | | -8+3(x-6)=1 | | -9(x+4)=18 | | 6(-3-x)+8=-16 |

Equations solver categories